Development of Guarantees in International Law - A. M. Ibragimov (Московский журнал международного права, 2008)
Origin and development of contractual practice in the period from ancient civilizations up to the end of the 18th century were accompanied by formation of various means of providing of execution of international contracts.For the purposes of realization of contractual establishments of the state during this period they used the reference to divine forces, the guarantee of the third states and Roman Catholic Church, institution of hostages, the fine for infringers of the contract, ratification, and institution of keepers of the contract, the international guarantees and other means.Despite of lacking of objective conditions for realization of means of providing of international contracts, these means have entered into the international practice, it was the forms of prompting to stop infringements of the legal obligations and in such quality in a small degree they provided certain contracts measure of behaviour of the states.In this sense they carried out function of international-legal guarantees as they could not be considered out of with them. Meanwhile international guarantees have actually arisen and started to function.